METODE DAKWAH USTADZ KHALID BASALAMAH DI AKUN YOUTUBE KHALID BASALAMAH OFFICIAL - Tri Mutiara (Jurnal Komunikasi, 2023)
Da'wah is an activity that invites people to the path of Allah, where in carrying out da'wah a da'i certainly requires a da'wah method to make it easier when carrying out da'wah. The da'wah method is a method used by a da'I when carrying out da'wah, so that what a preacher will convey is in accordance with his mad'u condition. This research was conducted to find out the method of preaching Ustadz Khalid Basalamah on the Khalid Basalamah Official YouTube account. To find out Ustadz Khalid Basalamah's da'wah method, this study used a qualitative method with a descriptive approach, by collecting data by observation and documentation. The results of the study showed that the da'wah method used by Ustadz Khalid Basalamah was the al- hikmah method, that is, he used a lot of arguments, hadiths, and stories of his companions in language that was easy for mad'u to understand. The al- mauizah hasanah method where he gave lots of invitations, advice, and education in a good way, where he conveyed it gently but also firmly